Aluminum–Nitrogen Interactions in the Soil–Plant System - Zhao, Xue Q.; Shen, Ren F. (Frontiers in Plant Science, 2018)
Aluminum (Al) is the most abundant metal in the Earth’s crust and is not an essential element for plant growth. In contrast, nitrogen (N) is the most important mineral element for plant growth, but this non-metal is often present at low levels in soils, and plants are often N deficient. Aluminum toxicity is dominant in acid soils, and so plants growing in acid soils have to overcome both Al toxicity and N limitation. Because of low N-use efficiency, large amounts of N fertilizers are applied to crop fields to achieve high yields, leading to soil acidification and potential Al toxicity. Aluminum lowers plant N uptake and N-use efficiency because Al inhibits root growth. Although numerous studies have investigated the interactions between Al and N, a complete review of these studies was lacking. This review describes: (1) the link between plant Al tolerance and ammonium/nitrate (NH4+/NO3-) preference; (2) the effects of NH4+/NO3- and pH on Al toxicity; (3) the effects of Al on soil N transformations; and (4) the effects of Al on NH4+/NO3- uptake and assimilation by plants. Acid soils are characterized chemically by a relatively high ratio of NH4+ to NO3- and high concentrations of toxic Al. Aluminum-tolerant plants generally prefer NH4+ as an N source, while Al-sensitive plants prefer NO3-. Compared with NO3-, NH4+ increases the solubilization of toxic Al into soil solutions, but NH4+ generally alleviates Al phytotoxicity under solution culture because the protons from NH4+ compete with Al3+ for adsorption sites on the root surface. Plant NO3- uptake and nitrate reductase activity are both inhibited by Al, while plant NH4+ uptake is inhibited to a smaller degree than NO3-. Together, the results of numerous studies indicate that there is a synergistic interaction between plant Al tolerance and NH4+ nutrition. This has important implications for the adaptation of plants to acid soils that are dominated chemically by toxic Al as well as NH4+. Finally, we discuss how this knowledge can be used to increase plant Al tolerance and N-use efficiency in acid soils.